Assessment of private sector spending in construction sector in South Africa: an auto-regression distributed lags approach / Adewumi Babalola, Fanie Buys and Ronney Ncwadi - Babalola, Adewumi; Buys, Fanie; Ncwadi, Ronney (Faculty of Architecture, Planning and Surveying, 2017)
This paper investigates the influence of macro-economic variables on the contribution of the private sector spending in construction sector to the South African economy. The methodology adopted for the study was an ex-post facto survey research because it was based on existing data. Annual data of the construction contributions, GDP, inflation rate and interest rate were collected between 1984 and 2011. The data were extracted from the published sources of the South African National Reserved Bank (SARB); Statistics South Africa (Stats. SA) and Quantec, South Africa. The study makes use of autoregressive distributed lags (ARDL) to prove that there is a long run causal relationship between private sector spending in construction and macroeconomic variables, namely, GDP, Real Exchange Rates, GDP in construction sector, interest rates and inflation rate in South Africa.